2009
DOI: 10.1128/aac.00035-09
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide Identification of Genetic Determinants of Antimicrobial Drug Resistance inPseudomonas aeruginosa

Abstract: The emergence of antimicrobial drug resistance is of enormous public concern due to the increased risk of delayed treatment of infections, the increased length of hospital stays, the substantial increase in the cost of care, and the high risk of fatal outcomes. A prerequisite for the development of effective therapy alternatives is a detailed understanding of the diversity of bacterial mechanisms that underlie drug resistance, especially for problematic gram-negative bacteria such as Pseudomonas aeruginosa. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
112
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(124 citation statements)
references
References 52 publications
6
112
2
1
Order By: Relevance
“…A single-amino-acid change in parE was found compared to the genome of PAO1, but this mutation has not been associated with resistance. It has been reported that mutations in the PAO1 genes PA1259 and PA2110 can lead to increased resistance to ciprofloxacin (12). The equivalents of these genes in the genome of isolate 39016 either are incomplete or are pseudogenes, which may explain the resistance phenotype.…”
Section: Distribution Of Clones Among the Keratitis Isolatesmentioning
confidence: 99%
“…A single-amino-acid change in parE was found compared to the genome of PAO1, but this mutation has not been associated with resistance. It has been reported that mutations in the PAO1 genes PA1259 and PA2110 can lead to increased resistance to ciprofloxacin (12). The equivalents of these genes in the genome of isolate 39016 either are incomplete or are pseudogenes, which may explain the resistance phenotype.…”
Section: Distribution Of Clones Among the Keratitis Isolatesmentioning
confidence: 99%
“…In favor of this hypothesis are the numerous reports indicating a modification of the oprF mutant against various classes of antibiotics. In P. aeruginosa PA14, loss of OprF induces susceptibility to a very broad spectrum of antimicrobials, such as carbapenem (ertapenem), cephalosporins (cefotaxime), aminoglycosides (levofloxacin), tetracyclines (tigecycline) (25), and also the fluoroquinolone ciprofloxacin (10). In their study, Woodruff and Hancock (68) showed that oprF mutant strain H636 was slightly more resistant to several ␤-lactam antibiotics, suggesting that the loss of OprF resulted in a modification of the OM structure, thus enhancing antibiotic uptake via nonporin pathways and counteracting the effects of the loss of OprF.…”
Section: Vol 79 2011mentioning
confidence: 99%
“…Recently, a number of resistomic studies have been carried out in P. aeruginosa (12)(13)(14)(15)(16)(17)(18). Genes of different functional classes have been identified to associate with intrinsic resistance against different types of antibiotics.…”
mentioning
confidence: 99%